Effect of Drumstick Leaves supplementation on Hematological Indices - Nambiar, Vanisha S (International Journal of Pharmaceutical & Biological Archive, 2010)
Background: Drumstick leaves (DL) with its high beta carotene content (19690 mcg/100g) along with vitamin C from lemon juice may have a positive impact in the mobilization of stored iron and increase hemoglobin levels of anemic subjects. Aim: To determine the effect of DL and vitamin C supplementation on hematological indices of young girls (16-21 years). Method: Based on pallor, 100/700 girls studying in first and second year the Faculty of Family and Community Sciences were selected and assessed for hematological Indices (Hb, Hct, PCV, MCV, MCHC) and red cell morphology and were divided into Group A (329 RE of Beta carotene from DL rich recipes (boiled mung/desi chana/kabuli chana) and 5.85 mg Vitamin C as lemon juice, n=21), Group B (329 RE from the above DL recipes, n=20) and Group C (recipes without DL leaves, n=21) for 45 days respectively. Results: Post supplementation data revealed 28.6% reduction of anemia in Group A, by followed by 5% in group B and 4.7% in group C. There was a positive change observed in red cell morphology (normocytic normochromic) in Group A (18%) and B (2.6%) respectively. Similar results were seen for RBC, MCV and MCHC. Group B which received drumstick leaves showed small positive change in MCH showing a causal association between VA and iron metabolism. Conclusions: The study emphasizes that anemia is still prevalent even in young adult women of the middle and high-income groups of urban Vadodara (54%). It also shows a strong association between vitamin C from lemon juice and iron and a causal association between VA available from DL and iron metabolism.